2005
DOI: 10.1248/jhs.51.394
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Murine Cytotoxic T Cells is Increased by High Molecular-Weight Fucoidan Extracted from Okinawa mozuku (Cladosiphon okamuranus)

Abstract: Male BALB/c mice were administered three fucoidans with different molecular weights prepared from Okinawa mozuku (Cladosiphon okamuranus). The proportion of CD8 + cells in the spleens of mice fed with high molecular-weight fucoidan significantly increased compared with those in mice fed a control diet. In addition, the CD4 + /CD8 + ratio tended to decrease and the proportion of CD11b + cells to increase. These results suggest that high molecular-weight fucoidan promotes an increase in the proportion of murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 14 publications
0
39
1
Order By: Relevance
“…Frequencies of HTLV-1-specific CD8(+) T-cells, natural killer cells, invariant natural killer T-cells and dendritic cells in the peripheral blood were analyzed but did not show significant changes. This contrasts with research in which fucoidan intake did alter immune parameters [33,40]. In this clinical study, there were mild side effects.…”
Section: Therapies From Fucoidancontrasting
confidence: 89%
“…Frequencies of HTLV-1-specific CD8(+) T-cells, natural killer cells, invariant natural killer T-cells and dendritic cells in the peripheral blood were analyzed but did not show significant changes. This contrasts with research in which fucoidan intake did alter immune parameters [33,40]. In this clinical study, there were mild side effects.…”
Section: Therapies From Fucoidancontrasting
confidence: 89%
“…Shimizu et al (2005) reported that high-molecular-weight fucoidan extracted from Okinawa mozuku changed the ratio of CD4 + /CD8 + and increased the ratio of cytotoxic T cells in mice splenocytes. In the present study, all fractions had higher molecular weights than those previously reported (Lee et al 2004) from the same source; the molecular weight of fucoidan determined by their study was 9,000 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is different to use fucoidan because of its high molecular weight causing the bioavailability to be lower (Shimizu et al 2005). Therefore, reducing the molecular weight of fucoidan has been a topic of research (Colliec et al 1991).…”
Section: Effect Of Lmw Fucoidan and Fucoidan On Cell Viabilitymentioning
confidence: 99%